The mARS complex: a critical mediator of immune regulation and homeostasis - Amanya, Sharon Bright; Oyewole-Said, Damilola; Ernste, Keenan J.; Bisht, Nalini; Murthy, Arnav; Vazquez-Perez, Jonathan; Konduri, Vanaja; Decker, William K. (Frontiers in Immunology, 2024)
Over the course of evolution, many proteins have undergone adaptive structural changes to meet the increasing homeostatic regulatory demands of multicellularity. Aminoacyl tRNA synthetases (aaRS), enzymes that catalyze the attachment of each amino acid to its cognate tRNA, are such proteins that have acquired new domains and motifs that enable non-canonical functions. Through these new domains and motifs, aaRS can assemble into large, multi-subunit complexes that enhance the efficiency of many biological functions. Moreover, because the complexity of multiaminoacyl tRNA synthetase (mARS) complexes increases with the corresponding complexity of higher eukaryotes, a contribution to regulation of homeostatic functions in multicellular organisms is hypothesized. While mARS complexes in lower eukaryotes may enhance efficiency of aminoacylation, little evidence exists to support a similar role in chordates or other higher eukaryotes.Rather, mARS complexes are reported to regulate multiple and variegated cellular processes that include angiogenesis, apoptosis, inflammation, anaphylaxis, and metabolism. Because all such processes are critical components of immune homeostasis, it is important to understand the role of mARS complexes in immune regulation. Here we provide a conceptual analysis of the current understanding of mARS complex dynamics and emerging mARS complex roles in immune regulation, the increased understanding of which should reveal therapeutic targets in immunity and immune-mediated disease.